Breaking the taboo: An exploration of female university students' experiences of attending a feminist‐informed sex education course - Askew, Julie (Sex Education : Sexuality, Society and Learning, 2007)
This article presents the results of a qualitative interview study of nine young women who attended a feminist-informed human sexuality course as undergraduate students at a US university located in the "Bible belt". The course focused on messages of desire and empowerment, rather than romance or fear, and was designed to encourage students to think critically about current sexual discourses. Results indicate that participants' information on sexual issues prior to taking the course was limited and largely negative. Experiences of the course are described in themes including owning sexual desire, improved body image, reduced guilt and fear, and increased confidence as a woman. It is concluded that sex education may be used to help empower female students and enrich their quality of life; current educational practices should therefore be examined for ways in which they are oppressive to development.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; corps; discipline; image corporelle; jeunes femmes*; pédagogie; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle; états-unis; étude qualitative

Mon/notre/leur corps est toujours un champ de bataille : discours féministes et queers libertaires au Québec, 2000-2007 - Breton, Émilie; Grolleau, Julie; Kruzynski, Anna; Saint-Arnaud-Babin1, Catherine (Recherches féministes, 2007)
Les auteures se livrent à une analyse des discours produits et diffusés par des groupes et des personnes qui luttent contre le patriarcat et l’hétérosexisme en priorité et qui semblent avoir une certaine culture libertaire. Une lecture des zines, des brochures, des journaux, des compilations vidéo/DVD, des albums de musique et des sites Web leur a permis de mettre en évidence trois tendances : la première regroupe les féministes radicales, clairement en continuité avec la génération politique précédente; la deuxième tendance s’apparente au women-of-color feminism; et la troisième est représentée par des groupes queers radicaux qui, tout en tentant de déconstruire l’identité sexuelle femme, invente un militantisme de multiples identifications.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; fem1000; hétérosexisme; militance; patriarcat; pratiques féministes; premier cycle; périodes historiques; queer; québec; ressource en ligne; régions géographiques; soc2014; systèmes d'oppressions; thématiques

Manifeste cyborg : science, technologie et féminisme socialiste à la fin du 20e siècle - Haraway, Donna Jeanne (Manifeste cyborg et autres essais : sciences, fictions, féminismes, 2007)
Keywords: amériques; approches et analyses; corps; cours; discours dominant; fem1000; féminisme cyborg; genre; identités LGBTQIA2+; point de vue situé; premier cycle; régions géographiques; systèmes d'oppressions; technologie; thématiques; états-unis

The master’s tools will never dismantle the master’s house - Lorde, Audre (Sister outsider: essays and speeches, 2007)
Keywords: afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; fem3600; féminisme afroaméricain; histoire et politique; lesbianisme; militance; premier cycle; régions géographiques; thématiques; émotions; états-unis; études littéraires